Evaluate the following:
x → 0 lim x 4 ∫ 0 x sin t 3 d t
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = x → 0 lim x 4 1 ∫ 0 x sin t 3 d t = x → 0 lim x 4 1 ∫ 0 x n = 0 ∑ ∞ ( 2 n + 1 ) ! ( − 1 ) n t 6 n + 3 d t = x → 0 lim x 4 1 n = 0 ∑ ∞ ∫ 0 x ( 2 n + 1 ) ! ( − 1 ) n t 6 n + 3 d t = x → 0 lim x 4 1 n = 0 ∑ ∞ ( 6 n + 4 ) ( 2 n + 1 ) ! ( − 1 ) n t 6 n + 4 ∣ ∣ ∣ ∣ 0 x = x → 0 lim x 4 1 n = 0 ∑ ∞ ( 6 n + 4 ) ( 2 n + 1 ) ! ( − 1 ) n x 6 n + 4 = x → 0 lim n = 0 ∑ ∞ ( 6 n + 4 ) ( 2 n + 1 ) ! ( − 1 ) n x 6 n = ( 6 ( 0 ) + 4 ) ( 2 ( 0 ) + 1 ) ! ( − 1 ) 0 = 4 1 By Maclaurin series
Nice solution.
Problem Loading...
Note Loading...
Set Loading...
The conditions of L'Hopital's Rule are satisfied, so that the required limit is:
lim x → 0 d x d ( x 4 ) d x d ∫ 0 x ( sin t 3 ) d t = lim x → 0 4 x 3 sin x 3 = lim x → 0 d x d ( 4 x 3 ) d x d ( sin x 3 ) = lim x → 0 1 2 x 2 3 x 2 cos x 3 = 4 1